2023
DOI: 10.3390/ijms241612753
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutation Status in Bulgarian Patients with Advanced and Metastatic Colorectal Cancer

Abstract: RAS somatic variants are predictors of resistance to anti-EGFR therapy for colorectal cancer (CRC) and affect the outcome of the disease. Our study aimed to evaluate the frequency of RAS, with a focus on KRAS variants, and their association with tumor location and some clinicopathological characteristics in Bulgarian CRC patients. We prospectively investigated 236 patients with advanced and metastatic CRC. Genomic DNA was extracted from FFPE tumor tissue samples, and commercially available kits were used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…The frequency of KRAS mutations (exon 2 and exon 3) in our cohort reached 61.88%. This was much higher than what was reported in the Asia-Pacific (37-52%) and Western populations (32-49%) [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Nevertheless, our data is in line with a previous study in Indonesia, showing that KRAS mutation was found in 71.8% of serrated adenocarcinoma (SA), which is intriguingly higher than the generally reported incidence of 40% [39][40][41].…”
Section: Discussionsupporting
confidence: 80%
“…The frequency of KRAS mutations (exon 2 and exon 3) in our cohort reached 61.88%. This was much higher than what was reported in the Asia-Pacific (37-52%) and Western populations (32-49%) [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Nevertheless, our data is in line with a previous study in Indonesia, showing that KRAS mutation was found in 71.8% of serrated adenocarcinoma (SA), which is intriguingly higher than the generally reported incidence of 40% [39][40][41].…”
Section: Discussionsupporting
confidence: 80%